2021
DOI: 10.1177/09697330211008634
|View full text |Cite
|
Sign up to set email alerts
|

Professional codes of conduct: A scoping review

Abstract: Background: Professional ethical codes are an important part of healthcare. They are part of the professionalisation of an occupation, are used for regulation of the professions and are intended to guide ethical behaviour in healthcare. However, so far, little is known about the practical use of professional codes in healthcare, particularly in paramedicine. Objective: The aim of this scoping review was to determine what is known in the existing literature about health professionals’ knowledge, awareness and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A recent scoping literature review was undertaken examining the use, knowledge and understanding of professional codes in medicine, paramedicine and nursing. 11 Despite the long history of professional codes within nursing and medicine, research from those professions shows that although clinicians highly value their codes as reflecting the collective values of the profession, they are poorly understood. 11 Even when practitioners value and understand their codes, the research showed that the codes are seldom used in clinical practice.…”
Section: The Role Of Professional Codes In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…A recent scoping literature review was undertaken examining the use, knowledge and understanding of professional codes in medicine, paramedicine and nursing. 11 Despite the long history of professional codes within nursing and medicine, research from those professions shows that although clinicians highly value their codes as reflecting the collective values of the profession, they are poorly understood. 11 Even when practitioners value and understand their codes, the research showed that the codes are seldom used in clinical practice.…”
Section: The Role Of Professional Codes In Healthcarementioning
confidence: 99%
“…11 Despite the long history of professional codes within nursing and medicine, research from those professions shows that although clinicians highly value their codes as reflecting the collective values of the profession, they are poorly understood. 11 Even when practitioners value and understand their codes, the research showed that the codes are seldom used in clinical practice. 12, 13 This is for a range of reasons, such as a lack of knowledge, workplace conflicts and institutional barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This is the key function of regulation (Reed, 2019). Several regulatory mechanisms can be used to this end including title protection, entry to practice standards, codes of conduct and regulatory standards creating clear boundaries for practitioners (Irvine, 2016; Moritz, 2019; Collings-Hughes et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%